You can publish your journal article! advice from editors to help you succeed - Gee, Gilbert C. (Sage, 2024)
"You've completed your research and want to publish it in a peer-reviewed journal. Author Gilbert C. Gee is here to help, sharing what he learned as a writer, reviewer, and Editor-in-Chief, and calling on other journal editors to offer their advice. You Can Publish Your Journal Article! will not only help you write your paper, but more importantly, be more likely to succeed in peer review. The book has four main premises: that writing involves a relationship between you and your readers, and that your research joins an ongoing conversation in the field; that good writing is rewriting, and revision is critical; that people who write daily are more productive than those who binge write; and finally, that persistency wins, so don't give up when you get a rejection. With chapters offering practical advice on selecting the right journal, peer review, the methods section, displaying your data, writing the results and discussion sections, the book concludes with short essays from invited journal editors about how to avoid common mistakes and ensure success"-- Provided by publisher.